2023
DOI: 10.1111/aji.13691
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of lncRNA and mRNA expression profiles in patients with unexplained recurrent spontaneous abortion

Abstract: Problem Unexplained recurrent spontaneous abortion (URSA) is one of the most frustrating and confounding conditions in reproductive medicine, and its exact pathogenesis has not been clearly established. Method of study In this study, we used RNA sequencing to characterize the mRNA and lncRNA expression profiles in peripheral blood. Thereafter, enrichment analysis was performed to determine the functions of the differentially expressed genes, and Cytoscape was used to construct lncRNA‐mRNA interaction networks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Efforts have been made to classify patients from an autoimmune perspective and provide graded treatment, with the aim of improving clinical outcomes 4–6 . Researchers have also employed a multi‐omics approach to identify biomarkers of pregnancy loss and predict reproductive aging, enabling clinicians to establish personalized therapeutic strategies 7–9 . Although researchers have found ways to manage and intervene clinically from an immune perspective in patients with clear immune alterations, the complexity of the national context and patient profile results in clinical design being subject to confounding factors and selection bias, leading to a relatively low level of evidence.…”
Section: Immunological Indicators For Predicting Pregnancy Failure An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been made to classify patients from an autoimmune perspective and provide graded treatment, with the aim of improving clinical outcomes 4–6 . Researchers have also employed a multi‐omics approach to identify biomarkers of pregnancy loss and predict reproductive aging, enabling clinicians to establish personalized therapeutic strategies 7–9 . Although researchers have found ways to manage and intervene clinically from an immune perspective in patients with clear immune alterations, the complexity of the national context and patient profile results in clinical design being subject to confounding factors and selection bias, leading to a relatively low level of evidence.…”
Section: Immunological Indicators For Predicting Pregnancy Failure An...mentioning
confidence: 99%
“…[4][5][6] Researchers have also employed a multi-omics approach to identify biomarkers of pregnancy loss and predict reproduc-tive aging, enabling clinicians to establish personalized therapeutic strategies. [7][8][9] Although researchers have found ways to manage and intervene clinically from an immune perspective in patients with clear immune alterations, the complexity of the national context and patient profile results in clinical design being subject to confounding factors and selection bias, leading to a relatively low level of evidence. For instance, intrauterine injection of hCG has been suggested to increase endometrial Tregs in patients with Treg-reduced repeat implantation failure (RIF) with concomitant improvement in pregnancy outcome.…”
Section: Immunological Indicators For Predicting Pregnancy Failure An...mentioning
confidence: 99%
“…coding gene PARPBP and terminates near the 5¢ end of the protein-coding gene IGF1 (van Dijk,Thulluru et al 2012, Frankish, Diekhans et al 2021). However, RNA-Seq read density suggests that transcription across the HELLPAR locus is not due to the expression of a single lncRNA.Rather, it appears to result from a combination of imprecise termination of the upstream PARPBP gene, leading to read-through transcription in the 5¢ half of the HELLPAR locus, and the transcription of a separate lncRNA, LINC02456, whose promoter is found in the center of the locus and whose transcribed product runs antisense through the IGF1 protein-coding gene (Figure4A;(Dunham, Kundaje et al 2012, de Goede, Nachun et al 2021, Zhu, Du et al 2023). Likewise, again visualizing short-read RNA-Seq data from(Dunham, Kundaje et al 2012, de Goede, Nachun et al 2021, we found examples of other XIST-like lncRNAs located in K562 expressed regions but whose transcript annotations were not strongly supported.…”
mentioning
confidence: 99%